Vagus nerve stimulation: mechanisms and factors involved in memory enhancement - Olsen, Laura K.; Solis, Ernesto; McIntire, Lindsey K.; Hatcher-Solis, Candice N. (Frontiers in Human Neuroscience, 2023)
Vagus nerve stimulation (VNS) has been recognized as a useful neuromodulation tool to target the central nervous system by electrical stimulation of peripheral nerves. Activation of the nucleus of the solitary tract (NTS) in the brainstem by vagal afferent nerve fibers allows for modulation of various higher order brain regions, including limbic and cerebral cortex structures. Along with neurological and psychiatric indications, clinical and preclinical studies suggest that VNS can improve memory. While the underlying mechanisms to improve memory with VNS involve brain areas, such as the prefrontal cortex and processes including alertness and arousal, here we focus on VNS-induced memory improvements related to the hippocampus, the main area implicated in memory acquisition. In addition, we detail research demonstrating that a targeted approach to VNS can modify memory outcomes and delve into the molecular mechanisms associated with these changes. These findings indicate that a greater understanding of VNS mechanisms while also considering administration site, timing in relation to training, and sex-specific factors, may allow for optimal VNS application to enhance memory.